2013
DOI: 10.1371/journal.pone.0072859
|View full text |Cite
|
Sign up to set email alerts
|

Valence and Arousal Ratings for 420 Finnish Nouns by Age and Gender

Abstract: Language-and culture-specific norms are needed for research on emotion-laden stimuli. We present valence and arousal ratings for 420 Finnish nouns for a sample of 996 Finnish speakers. Ratings are provided both for the whole sample and for subgroups divided by age and gender in light of previous research suggesting age- and gender-specific reactivity to the emotional content in stimuli. Moreover, corpus-based frequency values and word length are provided as objective psycholinguistic measures of the nouns. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
49
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 46 publications
10
49
1
2
Order By: Relevance
“…In line with prior reports (e.g., Gilet et al, 2012;Redondo et al, 2007), we found no differences between males' and females' ratings on the arousal dimension [Ms = 5.52 and 5.60, SDs = 1.49 and 2.17, respectively; t(874) = 1.84, p > .05]. However, higher mean arousal ratings have been observed in some studies (e.g., Soares et al, 2012;Söderholm, Häyry, Laine, & Karrasch, 2013).…”
Section: Gender Differencessupporting
confidence: 91%
“…In line with prior reports (e.g., Gilet et al, 2012;Redondo et al, 2007), we found no differences between males' and females' ratings on the arousal dimension [Ms = 5.52 and 5.60, SDs = 1.49 and 2.17, respectively; t(874) = 1.84, p > .05]. However, higher mean arousal ratings have been observed in some studies (e.g., Soares et al, 2012;Söderholm, Häyry, Laine, & Karrasch, 2013).…”
Section: Gender Differencessupporting
confidence: 91%
“…The lowest percentage corresponds to lowarousing negative words (e.g., desánimo, Bdespondency^). A similar distribution has been reported by Söderholm et al (2013) with a sample of 420 Finnish nouns.…”
Section: Exploration Of the Relationships Between Variablessupporting
confidence: 88%
“…In the normative studies investigating the affective properties of words, the most-used scale has been the Self-Assessment Manikin (SAM; Bradley & Lang, 1994), which is composed of 9 points accompanied by characters depicting the different anchor points. For the sake of comparability, and following the common procedure in the field (e.g., Ferré et al, 2012;Montefinese, Ambrosini, Fairfield, & Mammarella, 2014;Redondo et al, 2007;Soares, Comesaña, Pinheiro, Simões, & Frade, 2012;Söderholm, Häyry, Laine, & Karrasch, 2013), we adopted SAM as the rating scale, too. Participants rated the valences of words on a 9-point Likert scale ranging from completely sad(1) to completely happy(9).…”
Section: Methodsmentioning
confidence: 99%
“…This may be due to the fact that when aesthetic appeal is assessed (see the Aesthetic Appeal section above), that dimension already captures part of the positive-negative nature of the stimuli. However, since symbols may vary in the meanings they convey, it is also relevant to evaluate the valence associated with that meaning, as has been the case for words (e.g., Bradley & Lang, 1999a;Moors et al, 2013;Söderholm, Häyry, Laine, & Karrasch, 2013;Warriner, Kuperman, & Brysbaert, 2013). Like aesthetic appeal, valence is highly associated with familiarity.…”
Section: Dimensions Of Interestmentioning
confidence: 99%